Collective Knowledge How Teams and Larger Social Systems Learn, Remember, and Invent - Figge, Patrick (Innovation und Entrepreneurship,, 2018)
Collective knowledge and the associated concepts of collectively learning, remembering and inventing are increasingly important in today's economy and society. Completing knowledge work alone is more and more difficult for individuals. Based on novel datasets which identify founders as inventors on patents and survey data collected from senior management, the author investigates questions about knowledge processing. What determines whether dispersed specialist knowledge can be located and used to complete tasks or to create new knowledge? How are social interactions organized and to what extent do individuals such as founders influence the course of action taken by the system as a whole? Content Determinants of technological novelty in inventor teams Influence of Founder-Inventors, individual and team experience Development of Transactive Memory Systems Impact of social exchange patterns, costs of reciprocity and organizational design Transactive Memory Systems in the 'Digital Age' Target Groups Scientists, lecturers, and students in the areas of innovation and entrepreneurship, organization science, and strategy research Managers and practitioners in the fields of knowledge management, research & development, and digitalization The Author Dr. Patrick Figge received his Ph.D. from the University of Passau where he continues his research on entrepreneurship, teams/groups, and the impact of digitalization.